Exploring causes of streamflow alteration in the Medjerda river, Algeria - Mokrane Kadir; Raed Fehri; Doudja Souag; Marnik Vanclooster (Journal of Hydrology: Regional Studies, 2020)
Study region: The Medjerda is a transboundary catchment located in North-Eastern Algeria and shared with Tunisia. Study focus: In this study, we explore the causes of hydrological alteration of streamflow in a sub-catchment of the Medjerda in Algeria. The hydrological alteration was explored through the application of Mann-Kendall test based on possible explanatory factors, namely, precipitation, evapotranspiration, temperature, irrigation, and Normalized Difference of Vegetation Index (NDVI). Furthermore, the causal factors of streamflow variation were addressed using Convergent Cross Mapping (CCM) method. New hydrological insights for the region: Results of the trend analysis yield that the streamflow is altered during the period 1981−2012. This is consistent with the trends of the possible explanatory factors of this alteration. The Convergent Cross Mapping (CCM) method showed that streamflow alteration is unidirectionally caused by changes in patterns of precipitation, temperature, evapotranspiration, irrigation, and NDVI, and that there is little feedback from streamflow alteration to these causing factors. Overall, our assessment showed that the method used to identify the causal relationships in dynamical systems based on the CCM algorithm is suitable for exploring the drivers of the hydrologic alteration in multivariate time series, in particular when nonlinear dynamics determine the system.